The problem of the absurdity of human life in Truman Capote’s creative work - Chyrva, Yulia; Чирва, Юлія (Східноєвропейський національний університет ім. Лесі Українки, 2014)
The article deals with the theme which attracted Truman Capote: miserable people. The lonely alienated protagonist in Capote’s early works “Other Voices, Other Rooms”, “The Grass Harp”, “Breakfast at Tiffany’s” was finally realized in the nonfiction novel “In Cold Blood”. Perry Smith, a person with “torn” consciousness, realizes the unrealizability of his dreams, knows lies, pain, betrayal, sufferings that awaken feeling of loneliness, alienation, absurdity of being in his soul of a dreamer and define crisis “boundary” situation in which he finds himself. The essence of the philosophy of Smith’s image is that his fate doesn’t just state a fact that life is absurd but shows how these consequences become absurd. У статті осмисле¬но тему, котра найбільше приваблювала Т. Капоте: невлаштовані в суспільстві люди. Перрі Сміт, людина з «розірваною» свідомістю, усвідомлює нездійсненність своїх мрій, пізнає зраду, страждання, що цілком логічно породжують в його душі мрійника відчуття абсурдності існування. Його доля показує, як саме наслідки життя стають абсурдними.
Проблема абсурдності людського життя в творчості Трумена Капоте
Keywords: Truman Capote; absurd; alienation; loneliness; “Other Voices, Other Rooms”; “The Grass Harp”; “Breakfast at Tiffany’s”; “In Cold Blood”; Трумен Капоте, абсурд; відчуженість; самотність; «Інші голоси, інші кімнати»; «Трав’яна арфа»; «Сніданок у Тіффані»; «З холодним серцем»